Relation between motor and cognitive skills in Italian basketball players aged between 7 and 10 years old - Policastro, F.; Accardo, A.; Marcovich, R.; Pelamatti, G.; Zoia, S. (Sports, 2018)
There is evidence supporting a correlation between motor, attention and working memory in children. This present study focuses on children aged between 7 and 10 years, who have been playing basketball in the last two years. The aim of this study is to verify the correlation between cognitive and motor abilities and to understand the importance of this correlation in basketball practice. A total of 75 children who were 7.2-10.99 years old were assessed in terms of their attention, motor manual sequences and visuo-spatial working memory. A regression analysis was provided. In this sample, the motor abilities of children were found to be correlated with attention (denomination task, R2 = 0.07), visuo-spatial working memory (R2 = 0.06) and motor manual sequencing (aiming and catching task, R2 = 0.05; and manual dexterity task, R2 = 0.10). These correlations justify the suggestion to introduce deeper cognitive involvement during basketball training. The development of executive functions could have an important impact on basketball practice and the introduction of attention and memory tasks could help coaches to obtain optimal improvement in performance during the training sessions